Analysis of Fossil Fuel Subsidy Removal Policy in Nigeria - Adeforiti, Rotimi; Abang, Sunday Owen (Journal of Governance and Public Affairs, 2024)
Elite interest in energy policy reform has often been neglected in analysing subsidy removal policy on fossil fuel in Nigeria, which is the reason for this study. The study explained the reasons for the fossil fuel subsidy removal policy in Nigeria, identified the reasons for protests against fossil fuel subsidy removal policy in the country, and analysed the reasons for acceptance of protested fossil fuel subsidy removal policy in the country. Information for the study was obtained through a systematic review of 13 purposively selected peer-reviewed published journal articles between 1996 and 2023. Subsidy removal policy has been influenced by internal and external factors in Nigeria. Protests recorded against the policy have been noted to result from exploitation from the government and multinational oil companies, an increase in the poverty rate, an increase in the crime rate, a failed private investment quest, and a contradiction to the constitutional provisions on the welfare of the citizens. The acceptance of the policy is informed by the need to have sustainable access to fossil fuel, the capability of the government to provide services locally and nationally within the country, and the involvement of the labour unions in the negotiation on fuel subsidy removal. The study concluded that elite interest sustains subsidies removal policy on fossil fuel in the country